36 NEGATIVE PRESSURE PULMONARY EDEMA: CASE SERIES ANALYSIS. Issue 1 (1st January 2007) - Mulkey, Z.; Yarbrough, S.; Roongsritong, C.; Nugent, K.; Phy, M.
Abstract : Purpose of Study: Negative pressure pulmonary edema (NPPE) is an uncommon form of noncardiogenic pulmonary edema and is a complication of acute airway obstruction. This condition can occur postextubation and is usually recognized by the anesthesiologist. However, the general internist may not be aware of this syndrome and may be called to see these patients after they develop pulmonary edema. We wanted to review our cases to identify risk factors that could alert us to this possible complication. Methods: We retrospectively collected cases of NPPE from the pulmonary consult service over a span of 10 years. The hospital medical records of these cases were searched for information for risk factor analysis. Results: Twelve cases were collected and analyzed. The average age was 36.7 years; 10 patients were male. The average BMI was 25.4. None had documented previous lung disease, including asthma. Most of the operations were scheduled as outpatient procedures; the type of procedure ranged from an I&D of a bite wound to an ORIF of the radius. There were no otolaryngologic surgeries. The time for the procedure ranged from 27 to 335 minutes. Laryngospasm was the most commonly cited obstructing event (8/12). All patients had bilateral pulmonary infiltrates. The PO2 s ranged from 57 to 83 on FiO2 s from 35 to 100%. Treatment involved airway support with supplemental oxygen and usually diuresis. All patients survived. Conclusion: Postextubation pulmonary edema continues to occur 33 years after its initial description. Many patients have no obvious risk factor for upper airway obstruction. It often occurs in young, healthy patients with no underlying disease since this patient population has the muscular strength needed to create the highly negative intrathoracic pressures required to overcome the threshold for pulmonary microvascular damage. Other contributing factors described in the literature include obesity, short neck, obstructive sleep apnea, and upper airway surgery. The resulting edema can be life threatening if not recognized and treated quickly. Treatment involves maintaining a patent airway with adequate oxygenation, fluid restriction, and diuretics. Most patients respond quickly and are discharged within 3 to 4 days.